Acute Cardiac Injury in Coronavirus Disease 2019 and Other Viral Infections—A Systematic Review and Meta-Analysis. Issue 9 (September 2021) - Cheng, Matthew P.; Cau, Alessandro; Lee, Todd C.; Brodie, Daniel; Slutsky, Arthur; Marshall, John; Murthy, Srin; Lee, Terry; Singer, Joel; Demir, Koray K.; Boyd, John; Ohm, Hyejee; et al.
Abstract : OBJECTIVES: Severe acute respiratory syndrome–related coronavirus-2 binds and inhibits angiotensin-converting enzyme-2. The frequency of acute cardiac injury in patients with coronavirus disease 2019 is unknown. The objective was to compare the rates of cardiac injury by angiotensin-converting enzyme-2–binding viruses from viruses that do not bind to angiotensin-converting enzyme-2. DATA SOURCES: We performed a systematic review of coronavirus disease 2019 literature on PubMed and EMBASE. STUDY SELECTION: We included studies with ten or more hospitalized adults with confirmed coronavirus disease 2019 or other viral pathogens that described the occurrence of acute cardiac injury. This was defined by the original publication authors or by: 1) myocardial ischemia, 2) new cardiac arrhythmia on echocardiogram, or 3) new or worsening heart failure on echocardiogram. DATA EXTRACTION: We compared the rates of cardiac injury among patients with respiratory infections with viruses that down-regulate angiotensin-converting enzyme-2, including H1N1, H5N1, H7N9, and severe acute respiratory syndrome–related coronavirus-1, to those with respiratory infections from other influenza viruses that do not bind angiotensin-converting enzyme-2, including Influenza H3N2 and influenza B. DATA SYNTHESIS: Of 57 studies including 34, 072 patients, acute cardiac injury occurred in 50% (95% CI, 44–57%) of critically ill patients with coronavirus disease 2019. The overall risk of acute cardiac injury was 21% (95% CI, 18–26%) among hospitalized patients with coronavirus disease 2019. In comparison, 37% (95% CI, 26–49%) of critically ill patients with other respiratory viruses that bind angiotensin-converting enzyme-2 ( p = 0.061) and 12% (95% CI, 7–22%) of critically ill patients with other respiratory viruses that do not bind angiotensin-converting enzyme-2 ( p < 0.001) experienced a cardiac injury. CONCLUSIONS: Acute cardiac injury may be associated with whether the virus binds angiotensin-converting enzyme-2. Acute cardiac injury occurs in half of critically ill coronavirus disease 2019 patients, but only 12% of patients infected by viruses that do not bind to angiotensin-converting enzyme-2. Abstract : Supplemental Digital Content is available in the text.